If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(f + -5) = -16 Reorder the terms: 2(-5 + f) = -16 (-5 * 2 + f * 2) = -16 (-10 + 2f) = -16 Solving -10 + 2f = -16 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 2f = -16 + 10 Combine like terms: -10 + 10 = 0 0 + 2f = -16 + 10 2f = -16 + 10 Combine like terms: -16 + 10 = -6 2f = -6 Divide each side by '2'. f = -3 Simplifying f = -3
| 52=2v+16 | | 180x+75y=165 | | -2(x^2+3x+9)+3-9=0 | | -4q-17=-6q+43 | | 10d+d-9d-d=17 | | 3x+23=-2x-7 | | 3(4x+2)=10x-2 | | 14x-5=6x+1 | | 9x+1.2=-6x+7.3 | | 2tanx=7 | | -5g+2.5=18.8 | | 3g-2g+3=12 | | -2(x-5)+3=15 | | (x+5)3=36 | | 5(2l+4)=50 | | 9x^2-y^2+4=0 | | (U+5)*8=80 | | 2(a-3)=38 | | (u-6)8=24 | | 3+7t-4t+2-6= | | 0.6x+0.40(100-x)=50 | | (q-9)2=16 | | 4w^2-24w-7=0 | | (e+4)3=27 | | 3x^4=67 | | A+2b-8b= | | (Q-7)*5=25 | | -8q+18q+-13q=9 | | 2b+5j=8.43 | | 5x+101=13x-11 | | (e+5)*6=54 | | Y-5=3x-6 |